Clustering of the K⁺ channel GORK of Arabidopsis parallels its gating by extracellular K - Eisenach, Cornelia; Papanatsiou, Maria; Hillert, Ellin‐Kristina; Blatt, Michael R (The Plant journal : for cell and molecular biology, 2014)
GORK is the only outward‐rectifying Kv‐like K⁺ channel expressed in guard cells. Its activity is tightly regulated to facilitate K⁺ efflux for stomatal closure and is elevated in ABA in parallel with suppression of the activity of the inward‐rectifying K⁺ channel KAT1. Whereas the population of KAT1 is subject to regulated traffic to and from the plasma membrane, nothing is known about GORK, its distribution and traffic in vivo. We have used transformations with fluorescently‐tagged GORK to explore its characteristics in tobacco epidermis and Arabidopsis guard cells. These studies showed that GORK assembles in puncta that reversibly dissociated as a function of the external K⁺ concentration. Puncta dissociation parallelled the gating dependence of GORK, the speed of response consistent with the rapidity of channel gating response to changes in the external ionic conditions. Dissociation was also suppressed by the K⁺ channel blocker Ba²⁺. By contrast, confocal and protein biochemical analysis failed to uncover substantial exo‐ and endocytotic traffic of the channel. Gating of GORK is displaced to more positive voltages with external K⁺, a characteristic that ensures the channel facilitates only K⁺ efflux regardless of the external cation concentration. GORK conductance is also enhanced by external K⁺ above 1 mm. We suggest that GORK clustering in puncta is related to its gating and conductance, and reflects associated conformational changes and (de)stabilisation of the channel protein, possibly as a platform for transmission and coordination of channel gating in response to external K⁺.